Tricarboxylate Citrate Transporter of an Oleaginous Fungus Mucor circinelloides WJ11: From Function to Structure and Role in Lipid Production - Yang, Wu; Shah, Aabid Manzoor; Dong, Shiqi; Sun, Caili; Zhang, Huaiyuan; Mohamed, Hassan; Gao, Xiuzhen; Fan, Huirong; Song, Yuanda (Frontiers in Nutrition, 2021)
The citrate transporter protein (CTP) plays an important role in citrate efflux from the mitochondrial matrix to cytosol that has great importance in oleaginous fungi. The cytoplasmic citrate produced after citrate efflux serves as the primary carbon source for the triacylglycerol and cholesterol biosynthetic pathways. Because of the CTP's importance, our laboratory has extensively studied its structure/function relationships in Mucor circinelloides to comprehend its molecular mechanism. In the present study, the tricarboxylate citrate transporter (Tct) of M. circinelloides wj11 has been cloned, overexpressed, purified, kinetically and structurally characterized. The Tct protein of wj11 was expressed in Escherichia coli, isolated, and functionally reconstituted in a liposomal system for kinetic studies. Our results showed that Tct has a high affinity for citrate with Km 0.018 mM. Furthermore, the tct overexpression and knockout plasmids were created and transformed into M. circinelloides WJ11. The mitochondria of the tct-overexpressing transformant of M. circinelloides wj11 showed a 49% increase in citrate efflux, whereas the mitochondria of the tct-knockout transformant showed a 39% decrease in citrate efflux compared to the mitochondria of wild-type WJ11. To elucidate the structure-function relationship of this biologically important transporter a 3D model of the mitochondrial Tct protein was constructed using homology modeling. The overall structure of the protein is V-shaped and its 3D structure is dimeric. The transport stability of the structure was also assessed by molecular dynamics simulation studies. The activity domain was identified to form hydrogen bond and stacking interaction with citrate and malate upon docking. Tct has shown high binding energy of -4.87 kcal/mol to citric acid, while -3.80 kcal/mol to malic acid. This is the first report of unraveling the structural characteristics of WJ11 mitochondrial Tct protein and understanding the approach of the transporting towards its substrate. In conclusion, the present findings support our efforts to combine functional and structural data to better understand the Tct of M. circinelloides at the molecular level and its role in lipid accumulation.